The detection of concrete defects using infrared thermography - Sameh, Abdulrahman Arif (2017)
Advancement in the building diagnostics technologies and researches on the non-destructive test (NDT) which facilitate the detection of many complex cases such as cracking, deflection, bending and etc. Researches and experiments found that infrared thermography (IRT) is commonly used for structures diagnostics among the NDT methods, this method used for the detection of large area such as bridge decks, highways and airports. It’s basically conducted by measuring the radiant thermal energy which is released from the targeted object and could get a noticeable difference in measured temperature in the non-homogeneities region compared to homogametic. The aim of research is to discover and locate the defected parts in concrete such as cracks and honeycombs using infrared thermography camera. To analyze the defected parts, computers’ software has been used with aid of ultrasonic pulse velocity (UPV) test. This experiment has been done using concrete grade 30 by simulating the defects in concrete (crack and honeycomb) with sand reduction about 50% and 100% in order to simulate honeycomb in concrete cube samples. Samples were exposed to the sun and oven for different temperature before its photos taken by IRT IRT images shown defect zone can be seen by naked eyes. A computer software has been used to differentiate the concrete zone with problems by calculate the area of hue in HSB (hue, saturation and brightness) system which is representing the deference between defected and non-defected parts. After comparing shows that area of red colour in IRT image is less in defected concrete samples either cracks or honeycomb. As conclusion, IRT can be used to detect concrete problem such as crack and honeycomb at concrete structure and it can reduce inspection time for large area of concrete structures.